Oxygen profiles data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica - Ebner, Berenice; Henkel, Susann; Kraal, Peter; Müller, Daniel; Köster, Male; Staubwasser, Michael; Laufer-Meiser, Katja; Kattein, Laura; Geibert, Walter; Kasten, Sabine (In: Ebner, B et al. (2025): Oxygen profiles, pore-water- and solid phase data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986658, 2025)
During the PS133/2 research cruise with the German research vessel RV Polarstern in the austral summer of November and December 2022 into the Southern Ocean, sediment samples were collected using a multicorer at five stations and a handheld gravity corer (UWITEC) from a zodiac at two additional stations across two fjords in South Georgia: King Haakon Bay and Cumberland Bay. The main objective was to determine and quantify the different sources and transport pathways of iron from two fjords of South Georgia into the open ocean. A high resolution O2 profile was measured in five MUC cores using a fibre-optic oxygen microsensor (Pyroscience) to determine the oxygen penetration depths.
Keywords: Antarctica; iron; iron isotopes; marine biogeochemistry; nutrient; Oxygen; Pb-210 geochronology; sedimentary geochemistry; sulfate reduction rates